The Effect of Using Diorama Media on Learning Natural Appearances in Increasing Student Learning Motivation - Dinar Rafidah, Dita; Adha Salsabilah, Tian; Rustini, Tin (Journal of Education, 2025)
Learning media is one of the important components in supporting the implementation of learning. The use of learning media is needed to be able to overcome problems in the learning process. Learning media is very diverse. One type of learning media that is suitable for natural appearance material is diorama media. Diorama is a visual image in the form of mini size presented in three-dimensional form that aims to manipulate the actual scene. In learning the appearance of nature, diorama media can be used to increase student learning motivation, students can see directly how the difference between the type of natural appearance of land and natural appearance of water, on the type of natural appearance of land there are mountains, valleys, deserts etc., and on the type of natural appearance of water there are rivers, seas, lakes, etc. In the use of diorama media indirectly, students can see the difference between the type of natural appearance of land and water. In the use of diorama media indirectly students can learn actively and not easily bored because the media looks like a real picture so as to create learning activities that are not monotonous with that student learning motivation in this learning activity will increase learning motivation is a series of encouragement or driving force that comes from within oneself or from outside to carry out learning activities so as to cause changes.